Impact of a Palliative Care Nurse Practitioner in an Oncology Clinic: A Quality Improvement Effort. Issue 4 (8th April 2022) - D'Ambruoso, Sarah F.; Glaspy, John A.; Hurvitz, Sara A.; Wenger, Neil S.; Pietras, Christopher; Ahmed, Kauser; Drakaki, Alexandra; Goldman, Jonathan Wade; Anand, Sidharth; Simon, Wendy; Kung, Jennie; Coscarelli, Anne; et al.
Abstract : PURPOSE: Guidelines support early integration of palliative care (PC) into standard oncology practice; however, little is known as to whether outcomes can be improved by modifying health care delivery in a real-world setting. METHODS: We report our 6-year experience of embedding a nurse practitioner in an oncology clinic (March 2014-March 2020) to integrate early, concurrent advance care planning and PC. RESULTS: Compared with patients with advanced cancer not enrolled in the palliative care nurse practitioner program, in March 2020, patients who are enrolled are more likely to have higher quality of PC (eg, goals of care note documentation [82% v 15%; P < .01], referral to the psychosocial oncology program [67% v 37%; P < .01], and referral to hospice [61% v 34%; P < .01]) and less inpatient utilization in the last 6 months of life (eg, hospital days [12 v 18; P < .01] and intensive care unit days [1.2 v 2.3; P < .01]). The program expanded over time with the support of faculty skills training for advance care planning and PC, supporting a shared mental model of PC delivery within the oncology clinic. CONCLUSION: Embedding a trained palliative care nurse practitioner in oncology clinics to deliver early integrated PC can lead to improved quality of care for patients with advanced cancer. Abstract :